Co-drivers of air pollutant and CO2 emissions in China from 2000 to 2020 - Wenxin Cao; Yixuan Zheng; Shaohui Zhang; Zbigniew Klimont; Xian’en Wang; Fangming Jiang; Zhulin Qi; Chuchu Chen; Yueyi Feng; Zechen Zhang; Hongkuan Zang; Yu Lei; et al. (npj Climate and Atmospheric Science)
Abstract Revealing how historical energy and environmental policies interacted with socioeconomic factors to shape the trends in air pollutant and CO2 emissions is crucial for developing effective future pollution-carbon co-control strategies. Here, we develop an integrated analytical framework combining a detailed sectoral emission inventory, index decomposition analysis, and a clustering algorithm to investigate China’s synergetic patterns of air pollutant and CO2 emissions across 15 socioeconomic sectors from 2000 to 2020 and uncover the co-drivers behind these trends, with detailed temporal, sectoral, and spatial dynamics revealed. Our analysis suggests that historical policies have effectively curbed air pollutant emissions, while abating CO2 emissions remains a challenge. Energy and climate policies, particularly those focused on structural adjustments, are increasingly instrumental in driving pollution-carbon co-reduction. Compared to the earlier period, the fractional contribution of energy and climate policies to emission reductions of SO2, NO x , PM2.5, and CO2 increased by 1.3-8.6 times during 2010-2020, respectively. Substantial regional heterogeneity in emission co-drivers underscores the need for tailored strategies, such as adopting advanced energy-saving technologies in areas dominated by energy-intensive industries and accelerating the clean energy transition in regions endowed with renewable resources. Our study would provide actionable insights for formulating effective pollution-carbon co-control strategies in China and beyond.